Inflammatory diseases of the pelvic organs: modern standards of diagnosis and treatment - A. Z. Khashukoeva; M. I. Agaeva; Z. A. Agaeva; T. N. Savchenko; Yu. I. Lobacheva (Лечащий Врач, 2024)
Background. Inflammatory diseases of the pelvic organs occupy first place in the structure of gynecological diseases; the debut of inflammatory diseases in women occurs in most cases at a young age, increasing the risk of reproductive dysfunction, decreased fertility and decreased quality of life. The main symptoms of pelvic inflammatory diseases include periodic lower abdominal pain, increasing at the beginning or end of menstruation (often the intensity of pain does not correspond to changes in the reproductive organs); itching in the perineum; changes in libido, anorgasmia, vaginismus, dyspareunia; bleeding (mucous-purulent, mucous); urinary frequency and defecation disorders (a consequence of rectal dysfunction). Currently, the clinical picture of inflammatory diseases is characterized by a subacute onset, "erased" symptoms, varying severity of the course, which complicates their timely diagnosis and therapy. At the same time, there are discrepancies in the severity of the clinical course and the severity of the inflammatory process in organs and tissues. Late diagnosis and inadequate treatment of inflammatory diseases of the female genital organs significantly increases the frequency of adverse outcomes and the risk of reproductive losses among women.Conclusion. The problem of therapy of inflammatory diseases of the pelvic organs requires a comprehensive approach. An important component of treatment is antibacterial therapy. Taking into account modern standards of antibacterial therapy for inflammatory diseases of the pelvic organs, the following drugs deserve great attention: doxycycline and azithromycin in a dispersible form, which have improved pharmacokinetic properties, high efficiency and compliance.